Korelasi Keterampilan Membaca Pemahaman dengan Keterampilan Menulis Teks Tanggapan Siswa Kelas VII SMP - Tusyadiyah, Halimah; Amir, Amril; Afnita, Afnita; Anggraini, Dewi (Paedagogie, 2026)
The purpose of this study is to describe the following things. First, to describe the level of reading comprehension skills of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency. Second, to describe the level of writing response text skills of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency. Third, to describe the level of reading comprehension skills of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency. This type of research is quantitative with a descriptive method with a correlational design. The research design used is a correlational relationship between two variables. The population of this study was seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency registered in the 2025/2026 academic year with a total of 249 students. The sample in this study amounted to 71 students. The research sample was taken using the Slovin formula with a proportional random sampling technique. The research instrument was a test, namely an objective test of reading comprehension skills and a performance test of writing response text skills. There are three research results as follows. First, the reading comprehension skills of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency are in good qualifications with an average value of (76.67). Second, the writing skills of response texts of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency are in good qualifications with an average value of (82.51). Third, a significant correlation between reading comprehension skills and writing skills of response texts of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency at n-1 degrees of freedom (71-1) and a significance level of 95%, the h value (9.213) is greater than t table (1.669). Thus, it can be concluded that there is a significant correlation between reading comprehension skills and writing skills of response texts of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency. Keywords: Correlation, Reading Comprehension Skills, Writing Response Texts